The MediterrAsian way : a cookbook and guide to health, weight loss, and longevity, combining the best features of Mediterranean and Asian diets and l - Watson, Ric; Thelander, Trudy (Hoboken, New Jersey : John Wiley & Son, Inc., 2007)
In this unique cookbook and guide, Ric Watson and his wife, Trudy Thelander, demonstrate just how easy it is to realize the benefits of the MediterrAsian way-benefits that numerous scientific studies have documented over the last half century. They explain the common features of Mediterranean and Asian lifestyles-abundant amounts of plant foods and fish, small amounts of red meat, moderate alcohol consumption, physical activity, and time set aside to relax-and show you step by step how to make them part of your life. When you eat the MediterrAsian way, there's no skimping on taste-or satisfaction. You'll feast on more than 150 delicious recipes. You'll savor the intriguing flavors of Vietnamese Shrimp and Vegetable Rice Paper Rolls, Moroccan Stew with Couscous, and Teriyaki Chicken Noodles. And if you're in the mood for a burger or hot dog, Watson and Thelander offer several deliciously healthy versions. The book walks you through MediterrAsian food basics, shows you how to substitute daily activities for time at the gym, and explains how to take time out to enjoy life and relax. To help you plan your meals, it provides an easy-to-follow five-step MediterrAsian Balanced Meal System. There's even a fourteen-day MediterrAsian plan as well as example lifestyle scenarios to help you get into the swing of things. [from publisher description].
Unlocking the secrets of the Mediterranean diet and the Asian diet -- Fat fundamentals -- A feat of health from the sea -- Plant power -- Drink and be merry -- Stop exercising, starting living! -- A healthy mind in a healthy body -- The MediterrAsian balanced meal systm (MBMS) -- A 14-day example of healthy living -- Living the MediterrAsian way : eleven lifestyle scenarios -- Recipes: Pasta dishes ; Stir-fies ; Pizza ; Curries, stews, and baked dishes ; Rice and grain dishes ; Noodle dishes ; Sushi and rice paper rolls ; Grilled dishes ; Burgers and hot dogs ; Sandwiches and wraps ; Soups ; Salads ; Breakfasts ; Appetizers ; Sauces, dips, and spreads ; Desserts.
Includes bibliographical references (pages 299-304) and index.
Keywords: NUTRITION